01 ANALISIS PRODUKSI DAN PENDAPATAN USAHA GORENGAN 212 ALAUDDIN MAKASSAR - Jurnal Agribis; Andi Harnani; Syahdar Baba; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
The purpose of this research is to know the 212 fried food production process from fried food business in Alauddin Makassar, and to know the amount of income earned by fried food entrepreneurs from fried food business results. This research will be carried out at 212 Alauddin's fried food businesses in Makassar. This location was chosen with the consideration that the business is increasing so it is necessary to know the income. Answering the problem and testing the hypothesis a profit analysis method will be used. The production process of the 212 Alauddin Makassar fried food business is the distribution of raw materials and is processed to produce raw materials that are ready to be fried and produce fried foods. The income earned by 212 Alauddin Makassar fried foods is Rp. 5,303,000.